AICCRA 2022 Survey Results - final data - Schuetz, Tonja; Poulos, Allison; Cali', Davide; Ageyo, Collins Odhiambo; Giombini, Valentina (2023)
Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) is a USD 60 million three-year project, funded by the World Bank and being led by CIAT, with participating partners from six countries: Ethiopia, Kenya, Zambia, Ghana, Mali and Senegal. This report provides an overview of the Satisfaction Survey that was disseminated to partners to gather their feedback on three of the intermediate Project Indicators (IPI), as laid out in the Project Implementation Arrangements. These indicators capture progress on (1 - IPI 1.3) the satisfaction with the usefulness, accessibility and relevance, particularly for gender and youth responsiveness, (2 - IPI 2.4) effectiveness of partnerships and (3 - IPI 3.3) the use or adaptation of AICCRA-funded climate-relevant knowledge products, decision-making tools and services. The survey was open from 8 December 2022 to 11 January 2023 Cluster leads provided the products/services to survey for their cluster, and they sent the survey to their partners totalling 451 recipients. There were 312 responses from 309 unique individuals, which was a 69% response rate. Three individuals reported on two separate Clusters. All second year targets were achieved. Satisfaction with the products and services of the project (IPI 1.3) attained an average of 82%, 2% higher than the 2021 average of 80% and 5% higher than the target of 75%. Effectiveness of partnerships (IPI 2.4) surpassed the target of 75% and achieved an average score of 85% for all criteria including Vision, Leadership, Accountability, Communications & Collaboration and Impact, which matches the 2021 result. Through an elaborative capacity development program, IPI 3.3 - which looked precisely at how many respondents have used the products - scored an average of 73% confirmed use (233 identified use cases); well above the 12.5% target for year two. Continuous feedback on the survey design and results are also being compiled and will help improve the process for next year. (2022-12)